2017
DOI: 10.1007/s00701-016-3070-3
|View full text |Cite
|
Sign up to set email alerts
|

Middle cerebral artery aneurysms with intracerebral hematoma—the impact of side and volume on final outcome

Abstract: Our study confirms the benefit of the active treatment of patients with MCA aneurysms and associated ICH. A significant proportion of these patients achieves a favorable outcome. No association between the side of bleeding and outcome was demonstrated. Hematomas larger than 25 ml have a greater tendency to lead to an unfavorable outcome. The treatment decision-making process should not differ for either side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…In normal cerebral arteries, type IV collagen is mainly distributed in subendothelial BM, it can be seen with low expression around smooth muscle cell in media tunicae, the distribution of type IV collagen were destroyed on the wall of tumor, the expression of type IV collagen debated, distribution dispersion can be seen, all of these caused significant reduction of type IV collagen expression in original endothelium. Hemodynamics may also be an important factor which caused the occurrence and development of cerebral aneurysm, some researchers analyzed the rat model and found that on side ligaturing the cephalic artery can cause renal hypertension of rats, the occurrence of cystic aneurysm, spindle aneurysm can be seen after ligaturing the cephalic artery 12 months later, so we can conclude that the change of homodynamic has close correlation with the occurrence of aneurysm ( 10 – 12 ). Research has found that the pressure, shear stress and tensile stress all were arterial wall stress.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In normal cerebral arteries, type IV collagen is mainly distributed in subendothelial BM, it can be seen with low expression around smooth muscle cell in media tunicae, the distribution of type IV collagen were destroyed on the wall of tumor, the expression of type IV collagen debated, distribution dispersion can be seen, all of these caused significant reduction of type IV collagen expression in original endothelium. Hemodynamics may also be an important factor which caused the occurrence and development of cerebral aneurysm, some researchers analyzed the rat model and found that on side ligaturing the cephalic artery can cause renal hypertension of rats, the occurrence of cystic aneurysm, spindle aneurysm can be seen after ligaturing the cephalic artery 12 months later, so we can conclude that the change of homodynamic has close correlation with the occurrence of aneurysm ( 10 – 12 ). Research has found that the pressure, shear stress and tensile stress all were arterial wall stress.…”
Section: Discussionmentioning
confidence: 86%
“…In general, endothelial cells can change into biochemical reaction and electrophysiology when they meet mechanical force, leading to genetic expression changes and biological change. Some researchers pointed out that hemodynamic changes were the primary factors which caused the occurrence and development of aneurysml ( 12 14 ). It has been shown that internal pressure of aneurysm mainly act on the tumor wall and then cause the occurrence of stretch stress, and aneurysmal radius and intra tumor pressure all were positively correlated with stretch stress, stretch stress presented negative correlation with tumor wall thickness ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many diseases can affect the mechanical properties of brain tissue and cause neurological disorder, especially diseases that can form mass effect, such as cerebral tumor, cerebral cyst and ICH. Although there are few studies on the mass effect of ICH, the volume of hematoma, which is directly related to the mass effect, is recognized as one of the factors affecting clinical prognosis 22 . It has been reported that the mechanical disruption occurred immediately after ICH, and the main reason for the deterioration of pre-period ICH is the mass effect caused by haematoma enlargement 4 .…”
Section: Discussionmentioning
confidence: 99%
“…13 The major high-risk factors for ICH are an elderly population, 14 male sex, 15 current smoking, 16 excessive alcohol consumption, 17 low total cholesterol level, 18 long sleep duration, 19 illicit drug use, 20 Asians ethnic origin 21 and genetic factors. 22 Other clinical disease can cause ICH, including hypertension, 23 coagulopathy, 24 cerebral amyloid angiopathy (CAA), 25 cerebral tumours, 26 intracranial arterial aneurysm, 27 vascular anomalies, 28 brain trauma, 29 premature birth, 30 haemorrhagic conversion of stroke, 31 posterior reversible encephalopathy syndrome, 32 vasculitis, 33 infective endocarditis, 34 dural arteriovenous fistula, 35 brain arteriovenous malformation, 36 cavernous malformation 37 and intracranial venous thrombosis 38 (figure 1). ICH associated with hypertension remains the most common form of ICH.…”
Section: Ich In the Clinical Settingmentioning
confidence: 99%